(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
The present work shows an experimental investigation on the effect of minimum quantity cooling lubrication (MQCL) during hard turning of 90CrSi steel (60-62 HRC). The cooling strategy created by Ranque-Hilsch vortex tube combined with MQL ideal to from MQCL technique. Moreover, Al2O3 nanoparticles are suspended in soybean-based fluid to improve the lubricating character and retain the environmental friendly character. The response parameters, including cutting force and surface roughness are studied. The results of this work show that cutting performance of coated carbide tools improves due to the better cooling and lubricating effect. In addition, MQCL using Al2O3 nanofluid reduces the cutting forces significantly and shows the worse surface roughness compared MQCL with pure fluid. The promising results when using MQCL technique in hard machining will be a big step toward green manufacturing